Research on smallholder dairy production in coastal lowland Kenya - Thorpe, W.R.; Mullins, G.; Reynolds, L.; Maloo, S.H.; Muinga, R.W.; Mureithi, J.G.; Njuni, M.; Ramadhan, A. (International Livestock Centre for Africa, 1993)
This paper describes the origins and subsequent development of a collaborative programme of research on smallholder dairy production between KARI, ILCA and other cooperating institutions. The programme conducted research within a farming ystems framework in per-urban areas of coastal lowland Kenya. The integrated programme of on-farm and on-station research covers farming systems description and constraint identification, and technology development and testing. Major research areas centre on studies of milk consumption and marketing, smallholder resource management, disease risk to dairy cattle, feeding systems development and dairy cattle breeding. Results to date have confirmed the large milk deficit. East Coast fever has been shown to cause major losses in smallholder dairy cattle. The seasonal feed shortages and inadequate nutrient concentrations in milk produciton diets are being adressed through integrating crops and livestock by intercropping fodder grasses, maize and cassava with shrub and herbaceous legumes and the application of cattle manure. Rotational crossbreeding has been shown to be an efficient breeding system for smallholder milk production. Studies of current farming systems and the assessment of resource levels indicate that for the majority of households, agricultural change will be a sequential intensificaiton through the adoption of individual technological components rather than through the adoption of a multi-component package, such as the National Dairy Development Project's zero-grazing package.